Assessing trade-offs in U.S. military intervention decisions whether, when, and with what size force to intervene - Frederick, Bryan; Kavanagh, Jennifer 1981-; Pézard, Stéphanie; Stark, Alexandra; Chandler, Nathan 1982-; Hoobler, James; Kim, Jooeun (RAND Corporation, 2021)
"When faced with the outbreak of a war or the onset of an international crisis that affects important U.S. interests, U.S. policymakers must consider how best to respond. One option they may consider is to directly intervene militarily in the war or crisis. In this report, the authors create a framework that can be used to rigorously consider the trade-offs between intervening militarily early in a war or crisis, intervening later, and not intervening at all, as well as the trade-offs involved in decisions regarding the size of the potential intervention force to be employed. This framework can provide a better understanding of the relationships between intervention timing, intervention size, and intervention outcomes to inform future debates about whether and when to undertake a military intervention. The authors approached these issues in four ways. They conducted (1) an extensive review of academic and policy literature on relevant topics, (2) a quantitative analysis using a database of 286 crises and wars since 1945 in which important U.S. interests were at stake, (3) a set of 45 short, focused case studies, including both interventions and noninterventions, and (4) a set of four in-depth counterfactual illustrations, in which U.S. intervention decisions were altered from historical events to explore the implications. The findings from these four research approaches lead to recommendations regarding the contextual factors that are most essential for policymakers to consider when making intervention decisions."--Publisher's description
"Prepared for the United States Army."--Title page
"RAND Arroyo Center."--Title page
Keywords: Geschichte 1945-2021; Militärische Intervention; Sicherheitspolitik; USA; Intervention (International law); Intervention (International law) / Case studies; United States / Military policy; National security / United States; Military policy; National security; United States; Case studies